The interplay between critical transcription factors and microRNAs in the control of normal and malignant myelopoiesis. (28th July 2018) - Stavast, Christiaan J.; Leenen, Pieter J.M.; Erkeland, Stefan J.
Abstract: Myelopoiesis is a complex process driven by essential transcription factors, including C/EBPα, PU.1, RUNX1, KLF4 and IRF8. Together, these factors are critical for the control of myeloid progenitor cell expansion and lineage determination in the development of granulocytes and monocytes/macrophages. MicroRNAs (miRNAs) are expressed in a cell type and lineage specific manner. There is increasing evidence that miRNAs fine-tune the expression of hematopoietic lineage-specific transcription factors and drive the lineage decisions of hematopoietic progenitor cells. In this review, we discuss recently discovered self-activating and feed-back mechanisms in which transcription factors and miRNAs interact during myeloid cell development. Furthermore, we delineate how some of these mechanisms are affected in acute myeloid leukemia (AML) and how disrupted transcription factor-miRNA interplays contribute to leukemogenesis. Highlights: The interplay between transcription factors and microRNAs is critical for normal myelopoiesis. MicroRNAs control lineage decisions of hematopoietic progenitor cells. MicroRNA activities are frequently deregulated in acute myeloid leukemia.